Retorika Errol Jonathans Dalam Membangun Corporate Image Radio Suara Surabaya (Analisis Isi Video Pada Kanal Youtube TEDx Talks Edisi Tugu Pahlawan) - Arifin, M. Zainal; Oktarina, Riesta Ayu (DIGICOM : Jurnal Komunikasi dan Media, 2024)
Research on the communication activities of public figures, religion, politics, businessmen and other orators who represent certain groups, organizations or companies has been widely studied, but the phenomenon of communication from a company leader, especially in the media industry, is very minimally highlighted as a research object to be used as learning. The researcher analyzed Errol Jonathans' video rhetoric in building the corporate image of Suara Surabaya on the Tugu Pahlawan edition of the TEDx Talks Youtube channel. The researcher uses the content analysis method to describe the elements that tend to be highlighted by Errol Jonathans in building the company's image. This study focuses on analyzing the text content spoken in Errol Jonathans rhetoric videos. This study uses a theme analysis unit taken from the ideas of each paragraph. The purpose of this research is to find out that there are four categories of corporate image builders namely; personality, reputation, values ​​and corporate identity. The researcher describes the rhetorical forms of ethos, pathos, logos contained in Errol Jonathan's presentation. The results of this study are that Errol Jonathans tends to highlight the personality and reputation categories of the company in building a corporate image. The frequency of appearance of statements about company personality (59.37%), reputation (28.12%) then aspects of corporate values ​​and identity has a score of (6.25%). Another finding is that Errol Jonathan's presentation contains aspects of ethos, pathos and logos, the concepts put forward by Aristotle as art to persuade audiences.